Dynamic Load Balancing for Computational Grids using Binary Heaps (DLBCGBH – H / D) - Kumar, A; Pathak, H (International Journal of Computer Sciences and Engineering, 2025)
Grid Computing is a variant of distributed system wherein the small scale computational units are aggregated to develop a large computational machine to support complex computational problems. It poses a number of challenges for dynamic load balancing due to a large number of heterogeneous resources and the size of data to be moved among them thereby causing a number of issues to handle effectively. Further, load balancing problem in heterogeneous distributed computer systems is a NP-Hard problem. Therefore, researchers are constantly devising innovative approaches to optimize the load balancing in grid environment. In this paper, two algorithms for dynamic load balancing in computational grid viz. DLBCGBH - H & DLBCGBH – D are being described. These algorithms have already been implemented by the authors using GridSim 4.0 along with the comparison of the performance with the Built-in Space Shared utility of GridSim 4.0 for various performance metrics viz. Average Consumed Time, Average Waiting Time, Average Processing Cost and Number of Tasks Migrated.